THE ATTRACTIVENESS OF PRODUCT VARIATION, AND CLEANLINESS: ITS INFLUENCE ON PURCHASING DECISIONS AT SYAKILA BAKERY BENGKULU - Efan Tri Ahsyar; Andi Azhar (Suluh Adiluhung Publisher (SAPub), 2025)
This study aims to determine which factors are the most dominant in influencing purchasing decisions, the study was conducted briefly in November 2024. The sample of this study were consumers who had purchased products and knew Syakila Bakery. This study used a quantitative method on 25 respondents. The sampling technique was accidental sampling, the method used in this study was a quantitative method with Multiple Linear Regression analysis using SPSS 25 for windows. Based on the results of multiple linear regression, the regression equation form is Y = 3.195 + 8.805 (X1) + 6.175 (X2). The results of the study and the hypothesis in this study indicate that the variables of product variation and cleanliness have an attractiveness and have a positive effect, both partially and simultaneously, on purchasing decisions at Syakila Bakery.